Implementation of 3A in the Development of Kid's Forest Rides in Ragunan - Putri Maulida Fitria; Rizki Nurul Nugraha; Suadi Sapta Putra (West Science Interdisciplinary Studies, 2024)
This study aims to analyze the implementation of 3A (Attraction, Accessibility, Amenities) on the Kid's Forest vehicle in Ragunan. The research method used is qualitative, with a descriptive qualitative approach and SWOT analysis. Data collection through direct observation, interviews, and previous literature studies. The results showed that Kid's Forest rides offer diverse and interesting attractions, accessibility in Ragunan Zoo is very good, and adequate amenity. SWOT analysis shows that the strengths of Kid's Forest rides are attractive concepts, strategic locations, and adequate facilities. The weaknesses are the limited target market and the lack of educational facilities. Opportunities can further develop tourism activities and facilities. The most influential threat is bad weather that cannot be controlled, because the rides are outdoor activities. Strategies that can overcome these problems include developing wider attractions, improving the quality of facilities, more effective promotion, developing educational facilities, and evaluating weather conditions. By implementing these strategies, Kid's Forest at Ragunan Wildlife Park can increase its attractiveness, provide a better experience for visitors, and can contribute to sustainable tourism development in South Jakarta.